Avaliação dos efeitos dos metais pesados : uma abordagem ambiental em tartarugas marinhas expostas aos rejeitos da barragem de Mariana e experimental em zebrafish exposto ao chumbo - Miguel, Camila (2020)
In 2015, Brazil had its most notorious ecological disaster due to an iron mine dam collapse, in Minas Gerais state. The tailings composed mostly with iron ore and silica, but with high levels of heavy metals reached the Atlantic Ocean sixteen days after the accident. The region where the mud ran into the ocean, Doce River mouth, is an important nesting area for loggerhead turtles (Caretta caretta) in Brazil (Povoação, Espírito Santo state). The tailings also reached in important feeding area (Santa Cruz, Espírito Santo state) of juvenile green sea turtles (Chelonia mydas). The aim of this study was to evaluate the health and reproduction of sea turtles that live or occupy the areas affected by the tailings and compare with animals from an area that were not affected (Praia do Forte, Bahia state) or not directly affected (Coroa Vermelha, Bahia state). Health assessments were made throw a physical examination, hematological and biochemical analysis in both species. Heavy metal levels were quantified in the blood (both species), carapace, freshly eggs, unhatched eggs, and dead hatchlings of loggerhead turtles. Reproduction success were also analyzed in loggerhead turtles. Juvenile green sea turtles that feed in Santa Cruz had a worse nutritional status and higher degree of hepatic and renal lesions. Although not reflected in its corporal condition, the health status may indicate a physiological deficit that can affect their immune system and behavior, which is corroborated by the higher fibropapillomatosis tumor score and ectoparasite load in these animals. Adult loggerhead turtles from Povoação had higher As, Cd, Cr, Fe, Pb, and Zn levels in the blood and As, Cd, Cu, Fe, Hg, Mn e Hg levels in their eggs that remained in the nest until the end of the incubation period. Many correlations were found among the toxic elements and hematological and plasma biochemical analytes, and reproductive data suggesting that the exposure could be affecting the health and reproduction of these animals. Continued monitoring is very important to confirm if heavy metals from the mining dam rupture are influencing the health and reproduction of sea turtles that live and nest in this region. Additionally, the data reported here are important for spatial and temporal comparative studies in the future. This thesis also presents the results from a second project named “Lead effects on the development and behavior of zebrafish over three generations”. The motivation for this project was that biomarkers used in animal models can assist in development and implementation of similar approaches in animals that are difficult to rear in the laboratory, such as sea turtles. For that, the F0 generation organisms were exposed to 0 mg/L; 0.015 mg/L; 0.03mg/L; 0.06 mg/L and 0.1 mg/L of lead acetate (PbAc) during the first seven days of life and afterwards were reared in a metal-free environment. The animals in each group were mated to produce the F1 generation, which were used to produce the F2 generation. Only embryos of the F0 generation were exposed to the PbAc, while the subsequent generations were created in a metal-free environment. The results demonstrated that lead could cause behavioral changes and cardiotoxicity even after two generations without the exposure to the metal.